Polyphenylene-Based Solid Acid as an Efficient Catalyst for Activation and Hydration of Alkynes - Liu, Yiyun (Chem Mater, 2020)
[Image: see text] Porous polymer catalysts possess the potential to combine the advantages of heterogeneous and homogeneous catalysis, namely, easy postreaction recycling and high dispersion of active sites. Here, we designed a −SO(3)H functionalized polyphenylene (PPhen) framework with purely sp(2)-hybridized carbons, which exhibited high activity in the hydration of alkynes including challenging aliphatic substrates such as 1-octyne. The superiority of the structure lies in its covalent crosslink in the xy-plane with a π–π stacking interaction between the planes, enabling simultaneously high swellability and porosity (653 m(2)·g(–1)). High acidic site density (2.12 mmol·g(–1)) was achieved under a mild sulfonation condition. Similar turnover frequencies (0.015 ± 0.001 min(–1)) were obtained regardless of acidic density and crosslink content, suggesting high accessibility for all active sites over PPhen. In addition, the substituted benzene groups can activate alkynes through a T-shape CH/π interaction, as indicated by the 8 and 16 cm(–1) red shift of the alkyne C–H stretching peak for phenylacetylene and 1-octyne, respectively, in the infrared (IR) spectra. These advantages render PPhen-SO(3)H a promising candidate as a solid catalyst replacing the highly toxic liquid phase acids such as the mercury salt.